Comparative Legal Reasoning and European Law - Kiikeri, Markku. author. aut Link
XIII, 337 p.
Keywords: Comparative Legal Reasoning and European Law deals with the use of comparative law in European legal adjudication. It describes the different forms of the use of comparative law in legal reasoning, argumentation and justification in several national legal orders and in European level legal institutions. The book begins with an inquiry into the nature of comparative law as a legal source. After the description of the empirical study it ends to the general theory of European law and several hard cases of European law are examined. The book is intended for students and researchers in European law but it also contains aspects to be taken into account in the practical work in European legal orders and legal institutions by judges and legal practitioners.